2009
DOI: 10.1302/0301-620x.91b1.20899
|View full text |Cite|
|
Sign up to set email alerts
|

Unicompartmental or total knee replacement

Abstract: Between 1989 and 1992 we had 102 knees suitable for unicompartmental knee replacement (UKR). They were randomised to receive either a St Georg Sled UKR or a Kinematic modular total knee replacement (TKR). The early results demonstrated that the UKR group had less complications and more rapid rehabilitation than the TKR group. At five years there were an equal number of failures in the two groups but the UKR group had more excellent results and a greater range of movement. The cases were reviewed by a research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
79
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(86 citation statements)
references
References 35 publications
3
79
0
2
Order By: Relevance
“…We used the Norwegian version of the KOOS, which was published by Lygre and coworkers (2007). To our knowledge, only a few studies on functional results after UKR have involved follow-up at multiple time points (Kleijn et al 2007, Newman et al 2009), and none of them have used self-reported questionnaires. One of the strengths of our study is that we have included both short- and medium-term evaluations, which are necessary to establish a true timeline of functional recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the Norwegian version of the KOOS, which was published by Lygre and coworkers (2007). To our knowledge, only a few studies on functional results after UKR have involved follow-up at multiple time points (Kleijn et al 2007, Newman et al 2009), and none of them have used self-reported questionnaires. One of the strengths of our study is that we have included both short- and medium-term evaluations, which are necessary to establish a true timeline of functional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing UKR to total knee replacement (TKR) have shown faster recovery, shorter hospital stay, more normal kinematics, better range of motion, less blood loss, fewer thromboembolic incidents, and fewer surgical site infections (Li et al 2006, Walton et al 2006, Furnes et al 2007, Lombardi et al 2009, Newman et al 2009). Survival rates as high as 96–98% at 10 years have been reported in single-center studies (Murray et al 1998, Pandit et al 2011), whereas in studies from national arthroplasty registers 10-year survival rates have been reported to be as low as 80% (Furnes et al 2007, Koskinen et al 2008).…”
mentioning
confidence: 99%
“…However, no consistent results have been shown in these published randomized trials [5,20,23]. To the best of our knowledge, one meta-analysis [28] that compares UKA with TKA has been published over the past few years that pooled only one RCT study [19,20] with 6 other prospective cohort studies [2,6,12,15,17,27], and found that there was no clinically relevant or statistically significant improvement in UKA when compared to TKA. However, this meta-analysis did not consider sources of heterogeneity (e.g., preoperative range of motion, age, sex, and body mass index), and publication bias was not assessed.…”
Section: Introductionmentioning
confidence: 99%
“…There have been impressive survivorship studies, from both originator and non originator data, for the Oxford Unicompartmental Knee prosthesis, with rates of 94-100% at 10 years, and 95% at 14 years [1-5] and 90% at 15 years [6]. There are fewer studies describing the functional outcomes of this prosthesis [7-9].…”
Section: Introductionmentioning
confidence: 99%